IMPLEMENTASI METODE DESIGN THINKING PADA PERANCANGAN APLIKASI GAME EDUKASI PENCEGAHAN KEKERASAN SEKSUAL ANAK BERBASIS MULTIMEDIA - Siregar, Tara Naura (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
This research aims to serve as a useful supportive tool in providing knowledge to children about early sexual education to prevent sexual violence using interactive multimedia as an alternative solution for providing sex education to children. The sample for this research consists of fourth-grade students at SD Negeri Percobaan Medan. Through the Design Thinking approach, this research resulted in an educational android game application named "Aku Mandiri" which stands for "Aku Mampu Menjaga Diri". Testing methods included Pre-Test and Post-Test assessments. This research is intended that this application can support teachers and parents in providing effective sex education as a preventive measure against cases of sexual violence against children.